Boosting the low-temperature activity of Cu-SSZ-13 for NH3-SCR by mixing MnCeTiOx: The effect of nitrates on Cu redox cycle. Issue 6 (December 2022) - Li, Xinyu; Zhao, Huawang; Huang, Yating; Wu, Xiaomin; Huang, Zhiwei; Shen, Huazhen; Jing, Guohua
Abstract: A composite catalyst was prepared by mechanically mixing Cu-SSZ-13 and MnCeTiOx to improve selective catalytic reduction (SCR) of NOx by ammonia. The optimal mass ratio of Cu-SSZ-13 and MnCeTiOx components in the composite catalysts was 1:1, where the NOx conversion was improved by around 40% in the temperature range of 150–300 °C compared with Cu-SSZ-13 alone. MnCeTiOx presented significantly stronger ability on the activation of NO to nitrates species than Cu-SSZ-13. Infrared (IR) and density functional theory (DFT) results showed that active nitrates intermediate on MnCeTiOx might migrate to Cu-SSZ-13, which assisted the oxidation of single Cu + to Cu 2+ to complete the Cu redox cycle. This avoided the rate-determining step that formation and oxidation of Cu + dimers in low-temperature SCR over Cu-SSZ-13. The research results are beneficial to the rational design of SCR catalysts with high-performance at low temperatures. Highlights: Superior low-temperature performance achieved in MnCeTiOx /Cu-SSZ-13 hybrid catalysts. NO and NH3 were activated on MnCeTiOx and Cu-SSZ-13, respectively. NO was activated to nitrates by lattice oxygen in MnCeTiOx . Nitrates might transfer to the Cu-SSZ-13 and oxidize single Cu + directly. The accelerated redox cycle of Cu ions boosts low-temperature activity.